Articular Cartilage Degradation and Aberrant Subchondral Bone Remodeling in Patients with Osteoarthritis and Osteoporosis. (22nd November 2019) - Chu, Linyang; Liu, Xuqiang; He, Zihao; Han, Xuequan; Yan, Mengning; Qu, Xinhua; Li, Xiaofeng; Yu, Zhifeng
ABSTRACT: Osteoarthritis (OA) and osteoporosis (OP) are two skeletal disorders associated with joint structures. Occasionally, OA and OP occur in the same patient. However, the effect of OP changes on OA progression in patients with osteoporotic OA (OP‐OA) has not been reported, especially the potential association between subchondral bone and articular cartilage. Thus we investigated the alterations in the microstructure, biomechanical properties, and remodeling of subchondral bone as well as their association with cartilage damage in the hip joint of patients with OP‐OA. Thirty‐nine femoral head specimens were obtained from patients who underwent total hip arthroplasty (OA group, n  = 19; OP‐OA group, n  = 20), and healthy specimens from cadaver donors were used (control group, n  = 10). The microstructure and biomechanical properties of subchondral bone were evaluated by micro–computed tomography and micro–finite‐element analysis. Histology, histomorphometric measurements, and immunohistochemistry were used to assess subchondral bone remodeling and cartilage damage. Linear regression analysis was performed to elucidate the relationship between subchondral bone and articular cartilage. In the subchondral bone of the OP‐OA group, compared with that of the OA group, aberrant bone remodeling leads to an inferior microstructure and worsening biomechanical properties, potentially affecting transmission of loading stress from the cartilage to the subchondral bone, and then resulting in accelerated OA progression in patients with OP‐OA. The results indicate that changes in subchondral bone could affect OA development and the improvement in subchondral bone with bone‐metabolism agents may help mitigate OA progression when OP and OA coexist in the same patients. © 2019 American Society for Bone and Mineral Research.